Blockchain and Smart Contracts: Revolutionizing Auditing and Financial Transactions - Vanithamani M R, Dr. R. Nadanasabai, Dr. Saikumari.V, Dr; Ranjan Mishra, Dr. K. C. Prakash, Dr. Anurag Aeron, Dr. Biswo (Journal of Informatics Education and Research, 2024)
This paper explores the potential of blockchain technology to transform the accounting system. Blockchain technology is a distributed data set that records all exchanges in a shared organization, allowing for secure and dispersed transactions without relying on a centralized authority. It identifies challenges such as scalability, flexibility, suitable architecture, and cybersecurity. To fully integrate blockchain into an accounting ecosystem, a consensus between regulators and auditors is needed. The paper also provides an overview of how blockchain can improve information quality, highlighting its decentralization and transparency, which could significantly enhance the accounting system. In view of the discoveries from the overview, both brilliant agreement difficulties and open issues are distinguished to be tended to in additional examinations. At last, we talked about future patterns of shrewd agreements. This study offers educational help to partners intrigued by the exploration of shrewd agreements.